Preschoolers Mark Focus Types Through Multimodal Prominence: Further Evidence for the Precursor Role of Gestures - Sara Coego; Núria Esteve-Gibert; Pilar Prieto (Languages)
The present cross-sectional study assessed the role of multimodal cues in marking focus types during early childhood, focusing on prosodic prominence, gesture presence, and gestural prominence. A total of 116 Catalan-speaking three-, four- and five-year-olds participated in a semi-controlled interactive task eliciting words in three focus conditions: information, contrastive, and corrective. The data were coded manually using holistic assessments for all three measures. The results indicated, first, that children’s prosodic and gestural behavior was key in marking corrective focus. A significant tendency to use more gestures and increase both prosodic and gestural prominence was found in the corrective focus condition across the three age groups. Second, a developmental difference emerged in the acquisition of contrastive focus. Three-year-olds relied solely on gesture presence to encode contrastive focus, being unable to differentiate it prosodically from information focus. In turn, four- and five-year-olds used both gestures and prosody, with contrastive focus not only receiving more gestures than information focus but also increased prosodic prominence. This finding shows that gesture presence is a precursor to prosodic prominence in marking contrastive focus in Catalan, thus supporting the idea that gesture production can bootstrap the expression of focus type distinctions.